The dog stars [compact disc, unabridged] - Heller, Peter, 1959- (Random House Audio, 2012)
Hig survived the flu that killed everyone he knows. His wife is gone, his friends are dead, he lives in the hangar of a small abandoned airport with his dog, his only neighbor a gun-toting misanthrope. In his 1956 Cessna, Hig flies the perimeter of the airfield or sneaks off to the mountains to finsh and to pretend that things are the way they used to be. But when a random transmission somehow beams through his radio, the voice ignites a hope deep inside him that a better life, something like his old life, exists beyond the airport.